Effect of solar ultraviolet radiation exposure on serum 25(OH)D concentration: a pilot randomised controlled trial. Issue 5 (5th April 2018) - Khan, Shanchita R.; Whiteman, David C.; Kimlin, Michael G.; Janda, Monika; Clarke, Michael W.; Lucas, Robyn M.; Neale, Rachel E.
Abstract : A pilot trial investigated the change in serum 25(OH)D concentration induced by deliberate exposure to one SED of solar UV radiation. This will inform the methods of a fully powered trial. Abstract : Sunlight generates vitamin D, but there are scant human data from randomised trials on which to base health policy advice about how much sun exposure is necessary to change 25(OH)D concentrations. The purpose of the study was to evaluate the feasibility of using solar ultraviolet (UV) radiation exposure to generate a change in 25(OH)D concentration in a randomised controlled trial (RCT). The intervention tested in this RCT was supervised exposure to one standard erythemal dose (SED; 100 J m −2 ) of solar UV radiation three days per week for three weeks with approximately 35% of the body surface area not covered by clothing. Thirty-six fair-skinned (skin type II and III) indoor workers from Brisbane, Australia were randomised into either the intervention group ( n = 16) or the control group ( n = 20); the latter did not receive any supervised sun exposure. We asked both groups to use sunscreen and to minimise time outdoors during the study period. We collected blood samples at baseline, once per week during the three week intervention period, and four weeks after the intervention finished. The cumulative UV radiation exposure over the intervention period measured using polysulphone badges was higher in the intervention group than in the control group (median 8 vs. 4 SEDs, p = 0.14). After three weeks, the mean serum 25(OH)D concentration increased from 60 to 65 nmol l −1 in the intervention group and from 55 to 57 nmol l −1 in the control group. After adjustment for baseline 25(OH)D, the mean change per week during the intervention phase was non-significantly higher in the intervention than in the control group (0.7 vs. 0.3; p = 0.35). This difference was not sustained during the follow-up period. Large field trials are needed to inform policy about how much natural sun exposure is required to raise 25(OH)D concentrations. This pilot identified key issues that need to be considered in the design of such a trial.